Genomic and evolutionary aspects of phytoplasmas - Oshima, Kenro; Maejima, Kensaku; Namba, Shigetou (Frontiers in Microbiology, 2013)
Parasitic bacteria that infect eukaryotes, such as animals and plants, often have reduced genomes, having lost important metabolic genes as a result of their host-dependent life cycles. Genomic sequencing of these bacteria has revealed their survival strategies and adaptations to parasitism. Phytoplasmas (class Mollicutes, genus ‘Candidatus Phytoplasma’) are intracellular bacterial pathogens of plants and insects and cause devastating yield losses in diverse low- and high-value crops worldwide. The complete genomic sequences of 4 Candidatus Phytoplasma species have been reported. The genomes encode even fewer metabolic functions than other bacterial genomes do, which may be the result of reductive evolution as a consequence of their life as an intracellular parasite. This review summarizes current knowledge of the diversity and common features of phytoplasma genomes, including the factors responsible for pathogenicity.